Consumption of Lysozyme-Rich Milk Can Alter Microbial Fecal Populations - Maga, Elizabeth A. (American Society for Microbiology, 2012)
Human milk contains antimicrobial factors such as lysozyme and lactoferrin that are thought to contribute to the development of an intestinal microbiota beneficial to host health. However, these factors are lacking in the milk of dairy animals. Here we report the establishment of an animal model to allow the dissection of the role of milk components in gut microbiota modulation and subsequent changes in overall and intestinal health. Using milk from transgenic goats expressing human lysozyme at 68%, the level found in human milk and young pigs as feeding subjects, the fecal microbiota was analyzed over time using 16S rRNA gene sequencing and the G2 Phylochip. The two methods yielded similar results, with the G2 Phylochip giving more comprehensive information by detecting more OTUs. Total community populations remained similar within the feeding groups, and community member diversity was changed significantly upon consumption of lysozyme milk. Levels of Firmicutes (Clostridia) declined whereas those of Bacteroidetes increased over time in response to the consumption of lysozyme-rich milk. The proportions of these major phyla were significantly different (P < 0.05) from the proportions seen with control-fed animals after 14 days of feeding. Within phyla, the abundance of bacteria associated with gut health (Bifidobacteriaceae and Lactobacillaceae) increased and the abundance of those associated with disease (Mycobacteriaceae, Streptococcaceae, Campylobacterales) decreased with consumption of lysozyme milk. This study demonstrated that a single component of the diet with bioactivity changed the gut microbiome composition. Additionally, this model enabled the direct examination of the impact of lysozyme on beneficial microbe enrichment versus detrimental microbe reduction in the gut microbiome community.